Once‐weekly (70 mg/m(2)) vs twice‐weekly (56 mg/m(2)) dosing of carfilzomib in patients with relapsed or refractory multiple myeloma: A post hoc analysis of the ENDEAVOR, A.R.R.O.W., and CHAMPION‐1 trials - Moreau, Philippe (Cancer Med, 2020)
Combination of carfilzomib with dexamethasone (Kd) is approved for use in relapsed and/or refractory multiple myeloma (RRMM), with carfilzomib administered twice weekly at 56 mg/m(2) (Kd56 BIW) or once weekly at 70 mg/m(2) (Kd70 QW). Post hoc cross‐trial comparisons were performed to compare efficacy and safety profiles of Kd70 QW vs Kd56 BIW dosing schedules using data from three trials of patients with RRMM: A.R.R.O.W., CHAMPION‐1, and ENDEAVOR. To select for comparable patient populations, side‐by‐side efficacy and safety comparisons were performed in subgroups of patients with 2‐3 prior lines of therapy who were not refractory to bortezomib. The overall response rate (ORR) was 69.9% (95% confidence interval [CI], 61.7‐77.2) for Kd70 QW and 72.4% (95% CI, 65.9‐78.2) for Kd56 BIW. Median progression‐free survival (PFS) was 12.1 months (95% CI, 8.4‐14.3) for Kd70 QW and 14.5 months (95% CI, 10.2—not evaluable) for Kd56 BIW. Frequency of grade ≥ 3 adverse events (AEs) was 67.6% for Kd70 QW and 85.3% for Kd56 BIW. Regression analyses (adjusting for prognostic factors) of all patients in the trials who received Kd70 QW vs Kd56 BIW estimated a PFS hazard ratio of 0.91 (95% CI, 0.69‐1.19; P = .47) and an ORR odds ratio of 1.12 (95% CI, 0.74‐1.69; P = .61). These results suggest that Kd70 QW has a comparable efficacy profile compared with Kd56 BIW and represents a convenient and well‐tolerated treatment for patients with RRMM.